Investigations on the Biodiversity of Tropical Tasar silk moth (Antheraea Mylitta) in Uttar Pradesh - Jaipal Bhargava; Kalpana Singh (International Journal of Psychosocial Rehabilitation, 2020)
The Non-mulberry silk sector involves tropical and temperate Tasar silk. India is home to five types silk mulberry and non-mulberry silks viz. the tropical Tasar (Antheraea mylitta Drury), and temperate Tasar (Antheraea proyeli J), Muga (Antheraea assamensis Ww.) and Eri (Philosamia ricini Hutt.), All the five silks are produced by silk moths belong to family Saturniidae (order Lepidoptera). Tasar silkworms have stalled itself in several forms of environmental populations normally called as (ecoraces) in various geographical places of the country according to host plants and micro-environmental circumstances. In India Tasar species exists in the form of about 44 ecoraces. The present study, revealed that the diversity of profitable populations of Antheraea mylitta Drury in selected sites of Uttar Pradesh is dependent upon climatic conditions, physical geographics, and their cocoon characteristics vary accordingly.